Identificação de camarões de água doce coletados na região do Baixo Amazonas por meio de marcadores moleculares - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The shrimps are arthropods belonging to the subfamily Crustacea, order Decapoda, which in the Amazon are represented by 18 species distributed in 3 families (Euryrhynchidae, Palaemonidae and Sergestidae). But a diversity of prawns in the Lower Amazon region still needs to be better known. However, an identification by use of taxonomic keys is especially difficult due to the high degree of conservatism and intraspecific variation of the main characters analyzed. In the last 20 years, molecular biology techniques have contributed greatly to the resolution of doubts regarding the morphological variations that are generated by phenotypic plasticity, which would be related to distinct lineages. The present study aimed to identify, using mitochondrial and nuclear molecular markers, prawns collected in the Lower Amazon region. Obtaining the genetic material (total genomic DNA) was done by using the Wizard Genomic - Promega Kit. Partial sequences of the mitochondrial COI and 16S genes were obtained in both directions of the DNA strand, as well as partial sequences of the 28S nuclear gene. The sequences were aligned in the program CodonCode Aligner v7.0.1 (CodonCode Corporation). The analysis of inter and intraspecific genetic variability was made by calculating the p distance with evolutionary model Kimura 2 parameters (K2P) for the COI sequences. For the 16S and 28S markers the uncorrected p-distance was calculated. In all cases the MEGA v7.0 program was used. In addition, Neighbor Cluster trees (NJ) were also constructed using the MEGA v7.0 program. Of the 85 sequences obtained for COI, 39 showed signs of double peaks distributed among M. amazonicum and M. brasiliense species and were excluded from most analyzes. The analysis of the genetic distances associated to the analyzes of the phylogenetic trees obtained with the sequences without double peaks for the three markers, revealed new records for the region of Lower Amazon (PA) and state of Amazonas, Nhamundá municipality. These analyzes also suggested a new species in Macrobrachuim Bate, 1868 and another one in Palaemon Weber 1795.
Keywords: Camarões; Genética; Baixo Amazonas; CNPQ::CIÊNCIAS EXATAS E DA TERRA; ESTUDOS E MANEJOS DE ECOSSISTEMAS AMAZÔNICOS